Leadership Strategy for Tegal Warteg Business Development (Warteg) Rossa - Aulia Febriyanti; Nadia Septiani; Dwi Epty Hidayaty (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate effective leadership strategies for the business development of Warung Tegal (Warteg) Rossa. The research method used included literature study, interviews with the owner and manager of Warung Tegal (Warteg) Rossa, direct observation at the place of business, and analysis of quantitative and qualitative data. The results show that effective leadership practices in Warung Tegal (Warteg) Rossa involve the owner's or manager's active involvement in daily operations, good communication with employees, empowering employees, and developing a solid work team. The implementation of this leadership strategy has resulted in increased revenue, profit and sales growth in the business. This research contributes to the understanding of effective leadership strategies in the context of the Warung Tegal (Warteg) business and can be a reference for practitioners and researchers interested in developing micro-enterprises.